1986
DOI: 10.1177/070674378603100506
|View full text |Cite
|
Sign up to set email alerts
|

The Benefit of Lithium Carbonate Adjunct in Refractory Depression — Fact or Fiction?

Abstract: Our group attempted to validate previous claims of rapid success with lithium carbonate adjunct therapy in antidepressant-resistant depression. Seven depressed patients volunteered for a study of placebo controlled, double-blind design. During their treatment on general hospital psychiatric wards, these patients received antidepressant medication for a period of at least 21 days. While continuing to receive antidepressant medication after the 21 day period, four of the patients then received lithium carbonate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 5 publications
0
29
0
3
Order By: Relevance
“…67-82 a 4-week minimum duration of treatment; [74][75][76][77][78][79][80]81 or two or more failures of antidepressant therapy in the current episode of depression [67][68][69][70][71][72][73] (it is unclear how many trials in Crossley et al 60 are affected by this criterion). The results of both the Crossley et al 60 meta-analysis evaluating lithium compared with placebo augmentation and the Nelson et al…”
Section: Discussion and Summary Findingsmentioning
confidence: 99%
“…67-82 a 4-week minimum duration of treatment; [74][75][76][77][78][79][80]81 or two or more failures of antidepressant therapy in the current episode of depression [67][68][69][70][71][72][73] (it is unclear how many trials in Crossley et al 60 are affected by this criterion). The results of both the Crossley et al 60 meta-analysis evaluating lithium compared with placebo augmentation and the Nelson et al…”
Section: Discussion and Summary Findingsmentioning
confidence: 99%
“…Os estudos sobre DRT apresentaram problemas metodológicos importantes: utilização de diferentes definições de DRT; não-explicitação do critério de definição de resistência utilizado em ensaios (Goodwin et al, 1982;Kramlinger e Post, 1989); utilização de amostras insuficientes (De Montigny et al, 1983;Heninger et al, 1983;Cournoyer et al, 1984;Kantor et al, 1986;Zusky et al, 1988;Schopf et al, 1989;Kramlinger e Post, 1989;Dinan e Barry, 1989;Browne et al, 1990, Stein e Bernardt, 1993Baumann et al, 1996;Nierenberg et al, 2003;Maes et al, 1996;Moreno et al, 1997;Maes et al, 1999;Sokolski et al, 2004;Barbosa et al, 2003); realização de estudos não-controlados com placebo (Hoencamp, 1994;Fava et al, 1994Fava et al, e 2002Maes et al, 1999;Rybakowski et al, 1999;Corya et al, 2006); não-explicitação de inclusão (Maes et al, 1996;Maes et al, 1999;Sokolski et al, 2004), ou inclusão e análise em conjunto, de pacientes com história de episódio(s) de mania ou de hipomania (Heninger et al, 1983;Dinan e Barry, 1989;Schopf et al, 1989;Hoencamp et al, 1994;Katona et al, 1995;Baumann et al, 1996;Stein e Bernardt, 1993;Normann et al, 2002;Barbosa et al, 2003;Dubé et al, 2002a;…”
Section: Discussionunclassified
“…Entre os estudos, 14 utilizaram tricíclicos, seis utilizaram inibidores seletivos da recaptação da serotonina (ISRS), dois utilizaram inibidores da monoamina oxidase (IMAO) e dois utilizaram outras classes de antidepressivos. Dos 14 trabalhos envolvendo tricíclicos, nove utilizaram apenas esses fármacos (De Montigny et al, 1983;Cournoyer et al, 1984;Kantor et al, 1986;Dinan e Barry 1989;Browne et al, 1990;Stein e Bernardt 1993;Joffe et al, 1993;Hoencamp et al, 1994;Nierenberg et al, 2003) e cinco envolveram dois ou mais antidepressivos (Heninger et al, 1983;Zusky et al, 1988;Schopf et al, 1989;Katona et al, 1995;Rybakowski et al, 1999). Os IMAO foram utilizados em apenas dois ensaios, provavelmente devido ao fato de em geral serem empregados em etapas mais tardias da resistência ao tratamento e, também, devido aos riscos inerentes aos mesmos (Tabela 1).…”
Section: Lítiounclassified
See 1 more Smart Citation
“…However, few studies were conducted on SSRI nonresponders. Most of those studies were open label, and the results confirmed that augmentation with lithium was effective in TRD (Table 2) [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Level 1: Lithiummentioning
confidence: 96%